Religious and Academic Life in the Two Holy Mosques during the Tenth Century AH: A Historical Study in Light of the Book “Zad al-Muttaqin fī Suluk Tariq al-Yaqin” - Al-Nadwi, Sahibe Alam Al-Azmi (الدراسات الإسلامية, 2020)
The main purpose of this study is to investigate the religious and cultural circumstances in the Two Holy Mosques during the tenth century AH in light of the book “Zad al-Muttaqin fī Sulūk Tariq al-Yaqin,” compiled by Shaikh ‘Abd al-Ḥaqq Muḥaddith Dihlavi in Persian language, during his stay in Mecca and Medina. The paper deals with many topics such as the Shaikh’s biography and intellectual activities during his stay in India and in the Two Holy Mosques. It also aims to highlight his role in promoting the Islamic theology and the science of hadith in India. Moreover, it sheds light on the intellectual and religious works of the scholars and mystics who lived in the Two Holy Cities, in addition to many scholars and Sufis from Hejaz, Arab, and other Muslim countries. It also describes the religious environment of the Two Holy Mosques in the 10th century AH. Finally, the research discusses relations between religious scholars and mystics residing in the Two Holy Mosques and their intellectual, academic, and social interaction. Keywords Holy Mosques, Biographies, History, Religious Activities, Spiritual Life